PENGEMBANGAN MEDIA KARTU IDEKU UNTUK MENENTUKAN IDE POKOK PARAGRAF PADA SISWA KELAS IV MIM UNGGULAN KOTA GORONTALO - Siti Rahmatia Tuki; Wiwy T. Pulukadang; Fidyawati Monoarfa; Rusmin Husain; Rustam I. Husain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the difficulties fourth-grade students at MIM Unggulan Gorontalo City face in determining the main idea of paragraphs, as well as the limited learning media available to them. This study aims to identify the initial conditions of learning media in fourth-grade classes at MIM Unggulan Gorontalo City, examine the development process of Ideku Card media, and assess the feasibility of Ideku Card media in helping students determine the main idea of paragraphs. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results showed that the Ideku Card learning media was categorized as "highly feasible" based on validity testing, with high feasibility ratings from media (95%). language (90%), and material (90°) experts. Responses from teachers and students also indicated that this media is engaging, supports understanding, and increases students' activeness in determining the main idea of paragraphs. This is reflected in the teacher response reaching 100% and the student response averaging 90.37°. The overall average of 93% falls into the "highly feasible" category. Therefore, it can be concluded that the IdeKu Card media is a subjects on the topic of paragraph main ideas in the fourth grade teachers use this media to create active, interactive learning and t for other topics to make learning more varied.